Behavioral consistency of competitive behaviors and feeding patterns in lactating dairy cows across stocking densities at the feed bunk - Reyes, Faith S.; White, Heather M.; Weigel, Kent A.; Van Os, Jennifer M. C. (Frontiers in Veterinary Science, 2024)
High feed bunk stocking densities can differentially impact individual dairy cows’ competitive behaviors, feeding patterns, and feed efficiency. Our objective was to manipulate feed bunk stocking densities to evaluate intra-individual behavioral consistency across stocking densities and quantify associations with feed efficiency and production. Thirty-two primiparous (130.7±29.0 days in milk, DIM) and 32 multiparous (111.3±38.3 DIM) lactating Holstein cows were housed with 32 roughage intake control (RIC) bins. Each cow was assigned to share 8 bins with others of the same parity and similar body weight (16 cows/block; 2:1 feed bunk stocking density except during tests). Competition and feeding patterns were evaluated via video and RIC data, respectively, at 3 stocking densities (1:1, 2:1, 4:1 cows/bin) during 1-h tests (2 tests/stocking density; 6 tests/cow) following 2 h feed deprivation. Residual feed intake (RFI) was calculated across the 45-d study as the difference between observed and predicted dry matter intake (DMI) after accounting for known energy sinks. Linear mixed models were used to evaluate the overall impact of test stocking density on competition and feeding patterns. To evaluate intra-individual consistency between stocking densities, individual stability statistic (ISS) scores were computed. Correlational relationships were determined between RFI and ISS scores. Cows displayed the most competitive behaviors at 2:1 stocking density (P<0.0001) but experienced the highest rate of contacts per minute of eating time at 4:1 (1:1 vs. 2:1 vs. 4:1: 0.09 vs. 0.95 vs. 1.60 contacts/min; P<0.0001). Feeding patterns were modulated as stocking density increased; eating rate increased (0.16 vs. 0.18 vs. 0.22 kg/min; P<0.001) as eating time (40.3 vs. 28.2 vs. 14.6 min; P<0.001) and DMI decreased (6.3 vs. 5.1 vs. 3.0 kg; P<0.001). As stocking density doubled, individuals remained consistent (P=0.018) in time spent near others actively eating and tended to remain consistent in competition behavior and feeding patterns (0.053≤P≤ 0.094). Between 2:1 and 4:1, cows with high DMI and milk production were more consistent in first-visit DMI and duration. Feed efficiency was not associated with behavioral consistency across the tests (P≥0.14). Nonetheless, feed bunk stocking density has behavioral implications which should be considered in nutritional management decisions.